1998
DOI: 10.1073/pnas.95.11.6326
|View full text |Cite
|
Sign up to set email alerts
|

Abolition of morphine-immunosuppression in mice lacking the μ-opioid receptor gene

Abstract: Opiates are potent analgesic and addictive compounds. They also act on immune responses, and morphine, the prototypic opiate, has been repeatedly described as an immunosuppressive drug. Pharmacological studies have suggested that the inhibitory action of opiates on immunity is mediated by multiple opioid receptor sites but molecular evidence has remained elusive. Recently, three genes encoding -(MOR), ␦-, and -opioid receptors have been cloned. To investigate whether the -opioid receptor is functionally implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
85
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 26 publications
7
85
0
1
Order By: Relevance
“…[11][12][13]17 Opioid-induced splenocyte apoptosis was prevented by either opioid receptor antagonists or recombinant Fas-Ig or anti-FasL antibodies. 11,12 A similar opioid effect in adrenalectomized and sham-operated mice ruled out a mechanism dependent on the hypothalamicpituitary-adrenal axis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13]17 Opioid-induced splenocyte apoptosis was prevented by either opioid receptor antagonists or recombinant Fas-Ig or anti-FasL antibodies. 11,12 A similar opioid effect in adrenalectomized and sham-operated mice ruled out a mechanism dependent on the hypothalamicpituitary-adrenal axis.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 The major role of the MOR in the sensitization of splenocytes to Fas-mediated apoptosis was supported by the abrogation of the opioid-induced spleen atrophy in MOR knockout mice. 13,17 In vitro, experiments performed on immune cells-including lymphocytes and macrophages-showed that a direct interaction with morphine resulted in up-regulation of Fas mRNA. 11,18 Together, these data assume that spleen cell sensitization to Fas-mediated apoptosis induced by opioids was a paracrine/autocrine MOR-mediated effect associated with an increase in Fas mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, mor-null mouse studies have confirmed that MOR is involved in morphine immunosuppression (Gaveriaux-Ruff et al 1998;Roy et al 1998a). The transcription factor NF-κB is one of the most important transcription factors in immune cells (Li and Verma 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Three major mechanisms have been hypothesized for these effects: direct involvement of opioid receptors, hypothalamic pituitary adrenal (HPA) axis activation, and increased sympathetic nervous system activity. There is clear evidence for a role of opioid receptors, as mu-opiate receptor knockout (MORKO) animals did not display the same degree of immunosuppression as wildtype mice (Gavériaux-Ruff et al, 1998;Roy et al, 1998). Pharmacological studies have likewise implicated mu opiate receptors (e.g., Nelson et al, 2000; reviewed by Carr et al, 1996).…”
Section: Introductionmentioning
confidence: 99%